PLURALITY OF COUNTABLE NOUNS IN CHINESE AND INDONESIAN: MORPHOLOGICAL AND SYNTACTIC PERSPECTIVES WITH PEDAGOGICAL IMPLICATIONS - Idris, Hatmi (International Review of Humanities Studies, 2025)
This study investigates the plural meaning and expression of countable nouns in Chinese and Indonesian from morphological and syntactic perspectives and explores implications for language pedagogy. Although both languages encode plurality, they employ distinct mechanisms, which may pose challenges for Indonesian learners of Chinese. Using a qualitative, literature-based approach, data were drawn from scholarly studies, Chinese teaching materials, and reference sources such as dictionaries. Analysis focused on morphological markers, including affixation and reduplication, as well as syntactic structures, such as numeral–classifier phrases and quantifiers constructions. The findings show that Chinese expresses plurality through the suffix –men, classifier-based syntactic patterns, and quantifiers, whereas Indonesian primarily relies on reduplication, including noun and adjective reduplication, mechanisms that are limited or absent in Chinese. Indonesian can also employ quantifiers such as beberapa ‘some/several’ and classifier-based syntactic patterns, which partly overlap with Chinese strategies. These results highlight structural contrasts between the two languages and provide practical insights for teaching, and dictionary explanations aimed at Indonesian learners of Chinese.